Low‐loss and lightweight magnetic material for electrical machinery. Issue 2 (14th January 2020) - Ahmadi, Farzad; Sozer, Yilmaz; Donahue, Michael J.; Tsukerman, Igor
Abstract : A low‐loss and lightweight core material, with applications in electrical machinery, is made of highly packed and insulated magnetic microwires (MWs). These MWs are aligned in such a way as to guide the flux in the rotor/stator, with the ultimate goal of increasing the efficiency and substantially reducing core losses. Commercial F e bal N i 29 C o 17 ‐based MWs with a 127 μm diameter and a 33 μm insulation coating are utilised. The magnetic measurements of the fabricated sample demonstrate the high permeability and low core loss in a wide range of frequencies. To prove the utility of this type of material, the authors used it in the rotor core of a prototype 25 W three‐phase synchronous reluctance machine. The core is lighter and the losses are significantly lower than in conventional core materials under the same torque density.